Analisa Faktor yang Berhubungan dengan Pemanfaatan Pelayanan Kesehatan di Pesisir - Aina Cici Ramadhani; Susilawati Susilawati (Syntax Corporation Indonesia, 2022)
Utilization of health services is an important determinant of health, which is of particular concern as a public health and development problem in low-income countries. The World Health Organization (WHO) also recommends the use of medical services as a basic and primary health concept for the most vulnerable and disadvantaged. The purpose of this study was to identify factors related to the utilization of coastal health services. Data collection was taken from Google Scholar by using the keywords: factors, related, utilization and service. The research journal was taken in 2016-2020, then reviewed according to the inclusion and exclusion criteria applied by the author. The results of the literature show that there are variables of knowledge, tradition, attitude, accessibility, health workers, income and education with the use of health services for people in coastal areas.